2021
DOI: 10.1155/2021/8835704
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Knowledge and Dietary Intake Habits among Pregnant Adolescents Attending Antenatal Care Clinics in Urban Community in Ghana

Abstract: Introduction. Proper nutrition during pregnancy is important for the wellbeing of the mother and foetus and supports health during pregnancy, delivery, and breastfeeding. However, there are little data on nutritional knowledge and dietary intake among adolescents who are pregnant in Ghana. Hence, the study assessed the nutritional knowledge and eating habits of this vulnerable group in the Ledzokuku-Krowor Municipality, Ghana. Methods. The study was cross-sectional and employed a multistage sampling technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Although most of our participants (67%) reported that their diet had improved during the pregnancy, they did not have adequate dietary and nutrient intake or eating habits. Our participants’ dietary intake was low in legumes and vegetables and excessive in sweetened-sugar beverage consumption, which is common in most age groups [ 21 , 22 , 49 , 50 , 51 ]. More than 70% of pregnant adolescents did not eat more than three food groups in their meals.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of our participants (67%) reported that their diet had improved during the pregnancy, they did not have adequate dietary and nutrient intake or eating habits. Our participants’ dietary intake was low in legumes and vegetables and excessive in sweetened-sugar beverage consumption, which is common in most age groups [ 21 , 22 , 49 , 50 , 51 ]. More than 70% of pregnant adolescents did not eat more than three food groups in their meals.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the report of another study in Ghana where only 3.8% take F and V daily but contrasts with report from similar studies in Ireland (76%) and India (47%). [ 26 ] Many Nigerian women might not have information about the recommended number of servings of F and V or be unable to afford the adequate amount. Unfortunately, several micronutrients, which are important for mothers' health as well as baby's growth and development are largely obtained from fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that those pregnant women who attended 5-8 grades were less likely to practice optimal nutrition and health as compared to pregnant women who had no formal education. This finding is supported by the study done in Ghana that, those pregnant adolescents who did not go to school are more likely to be associated with good eating habits than those who attended school [40]. Since it is difficult to give the possible reasons, there is a need for further studies to ascertain contributory factors.…”
Section: Discussionmentioning
confidence: 66%